Efficacy and improvement of lipid profile after switching to rilpivirine in resource limited setting: real life clinical practice - Gatechompol, Sivaporn (AIDS Res Ther, 2019)
BACKGROUND: Long-term success of cART is possible if the regimen is convenient and less-toxic. This study assessed the efficacy and safety of switching from a first-line NNRTI or boosted PI-based regimens to RPV-based regimens among virologically suppressed participants in resource-limited setting (RLS). METHODS: This is a prospective cohort study. Participants with plasma HIV-RNA < 50 copies/mL receiving cART were switched from a PI- or NNRTI-based, to a RPV-based regimen between January 2011 and April 2018. The primary endpoint was the proportion of patients with plasma HIV-1 RNA level < 50 copies/mL after 12 months of RPV. The secondary endpoint was the virological response at 24 months and safety endpoint (change in lipid profiles and kidney function from baseline to 12 months). RESULTS: A total of 320 participants were enrolled into the study. The rationale for switching to RPV was based on toxicity of the current regimen (57%) or desire to simplify cART (41%). Totally, 177 (55%) and 143 (45%) participants were on NNRTI and boosted PI, respectively, prior to switching to RPV. After 12 months, 298 (93%) participants maintained virological suppression. There were significant improvements in the lipid parameters: TC (− 21 (IQR − 47 to 1) mg/dL; p < 0.001), LDL (− 14 (IQR − 37 to 11) mg/dL; p < 0.001) and TG (− 22 (IQR − 74 to 10) mg/dL; p < 0.001). Also, there was a small but statistically significant decrease in eGFR (− 4.3 (IQR − 12 to 1.1) mL/min per 1.73m2; p < 0.001). CONCLUSIONS: In RLS where integrase inhibitors are not affordable, RPV-based regimens are a good alternative option for PLHIV who cannot tolerate first-line NNRTI or boosted PI regimen, without prior NNRTI/PI resistance. Trial registration HIV-NAT 006 cohort, clinical trial number: NCT00411983